Dissemination of Artificial Preservatives for Food and Beverages at MA Al-Ishlah Jenggawah Jember: Sosialisasi Pengawet Buatan Untuk Makanan dan Minuman di MA Al-Ishlah Jenggawah Jember - Deyla Prajna; Angga Prasetyo; Shinta Widyaningtyas; Frengky Hermawan Hadi Prasetyo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The use of preservatives in food and beverages is common in the food industry to extend the shelf life of products. However, the misuse of synthetic preservatives that are not in accordance with the dosage or the use of illegal preservatives is still often found on the market. This socialization activity aims to increase the knowledge of MA Al-Ishlah Jenggawah Jember students regarding the types of preservatives, the risks of their use to health, and the ability to identify preservative content in food and beverage products. The methods used include delivering materials, object-based learning by observing product packaging labels, and interactive discussions. Evaluation was carried out through pre-test and post-test questionnaires to assess the increase in student understanding. The results showed a significant increase in participant understanding, both in terms of basic knowledge, product identification, and health impacts due to excessive consumption of preservatives. This activity shows that an interactive educational approach can increase students' awareness in choosing safer and healthier food.